VD_FINDINFO Pron / 2013 / 63 vom 12. März 2013 - VD Tribunal cantonal (2013)
TRANSACTION JUDICIAIRE, FRAIS JUDICIAIRES, RADIATION DU RÔLE | 109 al. 1 CPC (CH), 241 al. 2 CPC (CH), 67 al. 2 TFJC (2010)